BIG DATA and ANALYTICS in Accounting: Review and Synthesis of Research - T. N. Zverkova (Учёт. Анализ. Аудит)
This study’s relevance comes from adapting accounting for digital transformation and big data (BD). BD and big data analytics (BDA) are now widely accepted terms for large datasets. Analyzing and managing these datasets requires innovative methods. Accountants meet many obstacles when using analytical methods, hindering broader adoption. One of the fundamental difficulties is the insufficient adaptation of traditional accounting platforms to working with BD. Companies incur significant expenses for implementation and ongoing support. An added obstacle to the spread of data analytics in accounting is the conservatism of the profession itself. The paper’s goal is to study the problems and possibilities of using BD in accounting at the present stage. The author used general scientific methods, such as analysis, synthesis, and abstraction, to achieve the goal. The results of the study expand the scientific literature, providing a comprehensive analysis of BD in accounting. The work examined both the advantages and challenges that companies face when implementing these technologies. In ongoing digital transformation, full adoption and integration of BDA requires overcoming existing barriers, including technical aspects and the willingness of professionals to adapt to new requirements.